2023
DOI: 10.1186/s13148-023-01439-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of m7G regulator-mediated RNA methylation modification patterns and related immune microenvironment regulation characteristics in heart failure

Abstract: Background N7-methylguanosine (m7G) modification has been reported to regulate RNA expression in multiple pathophysiological processes. However, little is known about its role and association with immune microenvironment in heart failure (HF). Results One hundred twenty-four HF patients and 135 nonfailing donors (NFDs) from six microarray datasets in the gene expression omnibus (GEO) database were included to evaluate the expression profiles of m7G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…1 ). We collected 30 m7G regulator genes from previous studies [ 28 , 29 ] and are shown in Table S2 . The expression analysis identified 24 of the 30 m7G RNA regulator genes in human brain samples ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). We collected 30 m7G regulator genes from previous studies [ 28 , 29 ] and are shown in Table S2 . The expression analysis identified 24 of the 30 m7G RNA regulator genes in human brain samples ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2 ). Consensus clustering analysis classified 743 AD samples into different groups according to the m7G regulator genes [ 44 ]. We classified these samples into 2 to 10 subgroups ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation